2020
DOI: 10.3389/fpls.2020.00927
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Water and Nitrogen Use Efficiencies Through UAV-Based Multispectral Phenotyping in Winter Wheat

Abstract: Unmanned aerial vehicle (UAV) based remote sensing is a promising approach for nondestructive and high-throughput assessment of crop water and nitrogen (N) efficiencies. In this study, UAV was used to evaluate two field trials using four water (T0 = 0 mm, T1 = 80 mm, T2 = 120 mm, and T3 = 160 mm), and four N (T0 = 0, T1 = 120 kg ha −1 , T2 = 180 kg ha −1 , and T3 = 240 kg ha −1) treatments, respectively, conducted on three wheat genotypes at two locations. Ground-based destructive data of water and N indictors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
38
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 48 publications
(90 reference statements)
9
38
2
2
Order By: Relevance
“…1 ). Zhongmai 895 performed higher as compared to Yangmai 16 across the P treatments, as previously reported elite for high root growth at seedling stage and field-based nitrogen use efficiency [ 35 , 36 ]. SDW and RRS were negatively correlated across treatments (Fig.…”
Section: Discussionsupporting
confidence: 69%
“…1 ). Zhongmai 895 performed higher as compared to Yangmai 16 across the P treatments, as previously reported elite for high root growth at seedling stage and field-based nitrogen use efficiency [ 35 , 36 ]. SDW and RRS were negatively correlated across treatments (Fig.…”
Section: Discussionsupporting
confidence: 69%
“…These five VIs could be selected as the best ones to predict variations among the genotypes for grain yield. Previously, some studies have reported that GNDVI and NDRE were the best predictors for grain yield and nutrient uptake efficiencies across the growth stages [5,64]. Therefore, these VIs can be used to select high-yielding genotypes with high accuracy in large breeding programs.…”
Section: Discussionmentioning
confidence: 99%
“…The UAV-based multispectral vegetation indices have been increasingly exploited to predict plant physiological traits by crop breeding studies [5,64]. In this study, 20 VIs covering all five light bands captured by the multispectral sensor were taken to evaluate the machine learning models for grain yield prediction.…”
Section: Discussionmentioning
confidence: 99%
“…The application of UAV-based imaging techniques has been broadening in several areas of agricultural sciences thanks to their ability to analyze plant temperature and color discrepancies between distinct biological samples ( Padmavathi and Thangadurai, 2016 ; Cambaza et al, 2019 ). Many recent studies have exploited UAV-based sensors to monitor, detect and phenotype plant stresses in forestry ( Sagan et al, 2019 ), as well as to estimate leaf nitrogen concentration ( Lu et al, 2021 ), water and nitrogen use efficiencies ( Yang et al, 2020 ), and salinity stress ( Johansen et al, 2019 ) in different crops. Plant pathologists are recently also benefiting from the application of UAV-based sensors; in fact, UAV multispectral and hyperspectral imaging have been used to detect Xylella fastidiosa ( Castrignanò et al, 2021 ) and FHB ( Liu et al, 2020 ), respectively.…”
Section: Introductionmentioning
confidence: 99%